Decentralization as unbundling of public goods provision: New effects of decentralization on efficiency and electoral control - Antonio Farfán-Vallespín (University of Freiburg, Department of International Economic Policy (iep), 2012)
This paper proposes a new perspective for studying decentralization by considering it as the unbundling of public goods provision. We define centralization as the bundled provision of public goods from different tiers (national, sub-national or local) by one single provider held accountable by the voters via elections. We define decentralization as the unbundled provision of public goods of different tiers by a different provider for each tier, each of them accountable to the voters via elections. This novel perspective allows us to identify two new effects of decentralization. The first effect provides an efficiency advantage to centralization because the central provider can reallocate resources among the different tiers of public goods after shocks to the prices of these public goods occur. The second effect shows that unbundling the provision of public goods increases electoral control. Finally, we compare both effects and find that centralization will dominate over decentralization when public goods prices are more volatile and the option of transferring resources among tiers of public goods acts as an insurance device. Decentralization dominates when the environment is more stable and voters can monitor the providers of public goods more tightly.
Keywords: D74; K4; 330; decentralization; centralization; public goods; electoral control; Dezentralisierung; Öffentliche Güter; Versorgung; Leistungsbündel; Neue politische Ökonomie; Theorie